Countertransference : Theory, Technique, Teaching. - Alexandris, Athina (Karnac Books, 1998)
A collection of papers on the Oedipus complex, divided into three parts: theory, practice and supervision. Contributors include Joyce McDougall, Hanna Segal, Otto Kernberg and Leon Grinberg.